Magnetoacoustic Wave Dynamics and a Magnetic Null-Point - Zeinab Shajei; Zahra Fazel; Soheil Vasheghani Farahani; Hossein Ebadi (Iranian Journal of Astronomy and Astrophysics)
The solar wind acceleration and the coronal heating are two aspects of the solar atmosphere that comprise many physical phenomena. Some features of the solar atmosphere are somehow independent but some seem to be part of a chain reaction. In this study, the interaction of a magnetoacoustic pulse is highlighted with a two dimensional magnetic null point. A simple two dimensional magnetic null-point in the (x, y) plane is subject to a circlular pulse where its initial starting point depends on the solar atmospheric conditions. An analytic relation is presented that governs the density perturbations due to the nearing of the magnetoacoustic pulse. This enables a deeper insight on the effects of the zero and finite plasma-β conditions on the density perturbations. The analytic results are accompanied by numerical plots using the PLUTO code. The results indicate that finite plasma- β conditions decrease the plasma density at the magnetic null-point. This proves adequate for considering atmospheric conditions to prevent inaccurate conclusions regarding the interaction and energy transfer.